Social responsibility and professional ethics in management - Bavec, Cene (Managing global transitions, 2012)
In the presented exploratory study, we demonstrated some empirical evidences on relations between social responsibility of business, managerial ethics, and economic environment at county levels. We conducted desk research on 41 countries using different secondary information sources. We confirmed hypotheses, which associate higher social responsibility and ethics to openness and competitiveness of people and management, enhanced economic performance, higher economic freedom, and lower level of corruption. The rationale behind the research hypothesis is disputed question if socially responsible and ethically managed business is economically more successful and sustainable. Evidently, in the most developed countries unsocial and unethical business behavior is not generally acceptable. However, in less developed economies profit is so high on the priority list that social responsibility and ethics are academic questions.We hypothesize that companies consciously select where it is beneficial to be socially responsible and ethical, and where it is more profitable to make business ruthlessly. We also tested the hypothesis that social responsibility contributes to the resilience of economy. This hypothesis was partially confirmed and partially rejected. Finally, we addressed a question if our results are meaningful for individual organizations, as well.We could just say that more developed countries have a larger proportion of businesses that behave affirmatively regarding social and ethical issues, which means that they find it beneficial also at individual level.
Keywords: družbena odgovornost; management; ethics; etika; ekonomska učinkovitost; koruptivnost